PENGARUH PAJAK HOTEL DAN PAJAK RESTORAN TERHADAP PENDAPATAN ASLI DAERAH KOTA LHOKSEUMAWE - STIE Lhokseumawe (Sekolah Tinggi Ilmu Ekonomi Lhokseumawe, 2017)
This study aimed to test the hotel and restaurant tax on revenue Kota Lhokseumawe. The results of this study indicate that the Hotel and Restaurant Tax amounting to 2,570 temporary tcount ttable value is equal to 2.365. Tcount> ttable so this suggests that the Hotel and Restaurant Tax effect on regional revenue. The results of the study received the hypothesis Hotel and Restaurant Tax effect on the original income In the City of Lhokseumawe. Results koefisein correlation (R) of 0656, this value indicates the strength of relationship between hotel and restaurant taxes to increase regional revenue. So the relationship between the hotel and restaurant taxes to increase regional revenue in Lhokseumawe city government has a strong relationship in a positive, because positive values approaching 0,656 stu (+1). In addition to the value of the correlation coefficient (R) in table 4.5 also contained R-Square value of 0.430, this value known as the coefficient of determination. Through the coefficient of determination is known the influence of hotel and restaurant taxes to improve the original income in Lhokseumawe city government amounted to 43.0%. While the remaining 0.57 (57.0%) is the influence of other factors outside revenue.